Short-Term Exercise Training Improves Insulin Sensitivity but Does Not Inhibit Inflammatory Pathways in Immune Cells from Insulin-Resistant Subjects - Cersosimo, Eugenio; Reyna, Sara M.; Musi, Nicolas; Sriwijitkamol, Apiradee; DeFronzo, Ralph A.; Tantiwong, Puntip (Journal of diabetes research, 2013)
Background. Exercise has an anti-inflammatory effect against, and immune cells play critical roles in the development, of insulin resistance and atherosclerotic vascular disease (AVD). Thus, the goal of this study was to determine whether exercise improves insulin sensitivity in insulin-resistant subjects by downregulating proinflammatory signaling in immune cells. Methods. Seventeen lean, 8 obese nondiabetic, and 11 obese type 2 diabetic individuals underwent an aerobic exercise program for 15 days and an insulin clamp before and after exercise. Peripheral mononuclear cells (PMNC) were obtained for determination of Toll-like receptor (TLR) 2 and 4 protein content and mitogen-activated protein kinase phosphorylation. Results. Compared with that in lean individuals, TLR4 protein content was increased by 4.2-fold in diabetic subjects. This increase in TLR4 content was accompanied by a 3.0-fold increase in extracellular signal-regulated kinase (ERK) phosphorylation. Exercise improved insulin sensitivity in the lean, obese, and type 2 diabetes groups. However, exercise did not affect TLR content or ERK phosphorylation. Conclusions. TLR4 content and ERK phosphorylation are increased in PMNC of type 2 diabetic individuals. While exercise improves insulin sensitivity, this effect is not related to changes in TLR2/TLR4 content or ERK phosphorylation in PMNC of type 2 diabetic individuals.